High-strength composite material for manufacturing plastic shell and preparation method of high-strength composite material
By adding functional additives and composite flame retardant fillers to the polypropylene material, the polymer network and modified maifanite are solved, and the problems of low oxygen index, flammable and poor impact resistance of polypropylene material are achieved. Improved high strength, impact resistance, oxidation resistance and flame retardant performance, meet the various application needs of plastic shells.
Patent Information
- Application Number
- CN202411451753.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polypropylene materials have problems such as low oxygen index, combustible, poor impact resistance and mechanical properties in plastic shell applications, which limits their wide application.
70-85 parts of polypropylene, 4-10 parts of low-modulus polypropylene, 1-3 parts of compatibilizer, 0.5-1.5 parts of lubricant, 3-6 parts of functional additives, 2-5 parts of composite flame retardant filler The high-strength composite material forms a polymer network and modified maifanite through the preparation method of functional additives and composite flame retardant fillers, thereby improving the antioxidant and flame retardant properties of the material.
It significantly improves the impact resistance, flame retardant and oxidation resistance of composite materials, making the plastic shell more robust, prolongs service life, and meets a variety of application needs.
Smart Images

Figure CN119192728A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a high-strength composite material for manufacturing a plastic shell and a preparation method thereof. Background Art
[0002] With the continuous development and growth of the plastics industry, plastic shells have also entered the vision of all walks of life due to their many advantages. Compared with shells made of other materials, such as metal shells and glass shells, plastic shells have the advantages of light weight and low cost, which can meet the lightweight requirements of the industry. The design of plastic shells is flexible and diverse, and can be personalized according to different needs. There are more possibilities for innovation in product appearance and functionality. Therefore, plastic shells are widely used in electronic products, automotive industry, medical equipment, home appliance industry and other fields. They not only have good appearance design and aesthetics to meet the aesthetic needs of different users, but also have safety and reliability, protecting internal electronic components or mechanical materials from external environmental interference. Therefore, it is necessary to study the performance of plastic shell composite materials.
[0003] There are many kinds of materials for making plastic shells, such as polycarbonate (PC), polypropylene (PP), polyethylene terephthalate (PET), etc. Polypropylene materials have good chemical resistance, heat resistance and fatigue resistance, and are widely used in electronic product shells, electrical appliance shells, household items, etc. When used as electronic product and household appliance shells, polypropylene materials still have shortcomings. Polypropylene materials have a low oxygen index and are extremely easy to burn. In addition, they are easily affected by oxidation during long-term use. The impact resistance and mechanical properties are poor, which limits the application of polypropylene materials. Patent No. CN112225985B discloses a flame-retardant PP composite material and a preparation method thereof, including polypropylene, a compound flame retardant, a surface modifier, an antioxidant, a lubricant, and titanium dioxide. The prepared product has good flame retardancy and good processability, and is widely used in the fields of household appliances, automobiles, etc. However, when the patent is used as a material for manufacturing plastic shells, it has the disadvantage of poor impact resistance. Therefore, the present invention provides a high-strength composite material for manufacturing plastic shells, which meets various application requirements of plastic shells and has safety, reliability and broad application prospects. Summary of the invention
[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a high-strength composite material for manufacturing a plastic housing and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A high-strength composite material for manufacturing a plastic shell comprises the following raw materials in parts by weight: 70-85 parts of polypropylene, 4-10 parts of low modulus polypropylene, 1-3 parts of a compatibilizer, 0.5-1.5 parts of a lubricant, 3-6 parts of a functional additive, and 2-5 parts of a composite flame-retardant filler.
[0007] Furthermore, the compatibilizer is maleic anhydride grafted polypropylene; and the lubricant is any one of calcium stearate, magnesium stearate or zinc stearate.
[0008] Furthermore, the preparation method of the functional additive comprises the following steps:
[0009] S1. Add the terminal vinyl hyperbranched polyester, mercaptoethylamine and photoinitiator into toluene, stir evenly, and react under ultraviolet light for 1-3 hours. After the reaction is completed, separate the product to obtain an intermediate material;
[0010] S2. Add the intermediate material, anisaldehyde and triethylamine into methanol, stir evenly, and react for 2-4 hours at room temperature. After the reaction is completed, remove the solvent by distillation under reduced pressure, wash, and obtain a functional additive.
[0011] By adopting the above technical scheme, the vinyl group in the terminal vinyl hyperbranched polyester structure can undergo a thiol-ene click reaction with the thiol group in the thiolethylamine structure under the action of a photoinitiator to obtain an intermediate material. The intermediate material structure contains an active amino group, which can undergo a Schiff base reaction with the aldehyde group in anisaldehyde under the action of triethylamine to obtain a functional additive. The functional additive is obtained by grafting anisaldehyde, an antioxidant substance, onto terminal vinyl hyperbranched polyester. The generated Schiff base structure also has an antioxidant effect. Under the action of a compatibilizer, the functional additive can produce hydrogen bonds with a polypropylene matrix to form a polymer network. When subjected to external impact, the hyperbranched polyester can become a stress concentration point, triggering the formation of silver streaks and shear bands. The silver streaks and shear bands absorb a large amount of impact energy when expanding, and can withstand greater external impact without being easily damaged or broken, thereby improving the impact resistance of the composite material, thereby making the plastic shell more sturdy and durable. At the same time, it can avoid the precipitation of small molecule antioxidants, allowing the antioxidants to exist in the polypropylene matrix for a long time, thereby enhancing the antioxidant performance of the composite material, protecting the composite material from oxidation, and extending the service life of the plastic shell.
[0012] Furthermore, in S1, the photoinitiator is any one of benzoin bis ether, benzoin isobutyl ether or benzoin isopropyl ether.
[0013] Furthermore, the preparation method of the composite flame retardant filler comprises the following steps:
[0014] Step A, adding medical stone to a 0.5-1 mol / L hydrochloric acid solution, then placing the system in an ultrasonic cleaning machine for 10-15 minutes, filtering, washing, and drying to obtain activated medical stone;
[0015] Step B, uniformly dispersing the activated medical stone in N,N-dimethylformamide, introducing nitrogen, adding 6-chloropyridine-3-carbonyl chloride and a catalyst, stirring at room temperature for 5-6 hours, filtering, washing, and drying to obtain modified medical stone;
[0016] Step C, adding modified medical stone to dimethyl sulfoxide, stirring evenly, introducing nitrogen, adding dimethyl hydroxymethylphosphonate and an alkaline catalyst, heating to 60-80° C., stirring for 6-8 hours, centrifuging, washing, and drying to obtain a composite flame retardant filler.
[0017] By adopting the above technical scheme, after being activated by a hydrochloric acid solution, the medical stone can expose more hydroxyl groups. Under the action of a catalyst, the hydroxyl groups on the surface of the activated medical stone can undergo an esterification reaction with the acyl chloride in the structure of 6-chloropyridine-3-carbonyl chloride to obtain modified medical stone. Under the action of an alkaline catalyst, the active chlorine substituents on the surface of the modified medical stone can undergo a substitution reaction with the hydroxyl groups in the structure of dimethyl hydroxymethylphosphonate to obtain a composite flame retardant filler. The composite flame retardant filler uses medical stone as a base material. After modification, it can effectively improve the compatibility with the polypropylene base, avoid the agglomeration of medical stone in the polypropylene base, and can be evenly dispersed in the polypropylene base, thereby effectively exerting the advantages of medical stone and enhancing the mechanical properties of the polypropylene base. In addition, medical stone can absorb a large amount of heat, form a heat insulation layer on the surface of the composite material, isolate heat and oxygen, and slow down the combustion rate. At the same time, the composite flame retardant filler contains nitrogen and phosphorus flame retardant elements, which can play a synergistic role in the gas phase and the condensed phase to form a dense carbon layer and dilute the combustible gas. Medical stone can produce a synergistic effect with it, making it difficult to continue combustion, enhancing the flame retardant properties of the composite material, and thus improving the safety and reliability of the plastic shell.
[0018] Furthermore, in step B, the catalyst is pyridine or triethylamine.
[0019] Furthermore, in step C, the alkaline catalyst is potassium carbonate or sodium carbonate.
[0020] A method for preparing a high-strength composite material for manufacturing a plastic housing comprises the following steps:
[0021] Step 1: Add polypropylene, low modulus polypropylene, compatibilizer, lubricant, functional additive and composite flame retardant filler into a high speed mixer, set the stirring speed to 300-600 r / min, stir and mix for 25-40 minutes, and obtain a mixed material;
[0022] Step 2: Add the mixed material into a twin-screw extruder, and obtain a composite material through melting, extrusion and granulation.
[0023] Furthermore, the twin-screw extruder has a melting temperature of 160-200° C. and a screw speed of 200-500 r / min.
[0024] Beneficial effects of the present invention:
[0025] The present invention uses polypropylene material as the matrix, and by adding functional additives and composite flame retardant fillers, the impact strength of the prepared composite material can reach 42.3KJ / m 2 The tensile strength can reach 32.5MPa, the oxygen index can reach 33.7%, it has high strength and excellent impact resistance, and is not easily damaged or broken by external impact. The plastic shell made of composite materials is more durable and has excellent flame retardant properties. It also has excellent antioxidant properties, which can extend the service life of the plastic shell and meet the various application needs of the plastic shell. It has safety, reliability and broad application prospects.
[0026] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0028] Figure 1 The infrared spectrum of the functional additive prepared by the present invention;
[0029] Figure 2 This is the infrared spectrum of the composite flame retardant filler prepared by the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The preparation methods of the functional additives in the following examples and comparative examples of the present invention are as follows:
[0032] S1, adding 3.4g of terminal vinyl hyperbranched polyester, 2.8g of mercaptoethylamine and 0.3g of benzoin dimethyl ether into toluene, stirring evenly, reacting under ultraviolet light for 3h, and after the reaction is completed, separating the product to obtain an intermediate material;
[0033] S2. Add 3 g of the intermediate material, 2.5 g of anisaldehyde and 0.4 g of triethylamine into methanol, stir evenly, and react at room temperature for 4 h. After the reaction is completed, remove the solvent by distillation under reduced pressure, wash, and obtain a functional additive.
[0034] Use Nicoletis50 Fourier transform infrared spectrometer to conduct infrared test on functional additives, such as Figure 1 As shown in the figure, analysis shows that in the infrared spectrum of the functional additives, 3070-3020cm -1 The absorption peak of CH in the benzene ring appeared at 1732 cm -1 The absorption peak of ester group C=O appeared at 1632 cm -1 The absorption peak of Schiff base C=N appeared at 1252 cm -1 The absorption peak of CO appeared at 1195 cm -1 The absorption peak of CSC appears at .
[0035] The preparation methods of the composite flame retardant fillers in the following examples and comparative examples of the present invention are as follows:
[0036] Step A, adding medical stone to 1 mol / L hydrochloric acid solution, then placing the system in an ultrasonic cleaning machine for 15 minutes, filtering, washing, and drying to obtain activated medical stone;
[0037] Step B, 3.2 g of activated medical stone is uniformly dispersed in N, N-dimethylformamide, nitrogen is introduced, 2.6 g of 6-chloropyridine-3-carbonyl chloride and 0.4 g of triethylamine are added, and after stirring at room temperature for 6 h, the mixture is filtered, washed, and dried to obtain modified medical stone;
[0038] Step C, add 2.8g of modified medical stone to dimethyl sulfoxide, stir evenly, introduce nitrogen, add 2.5g of dimethyl hydroxymethylphosphonate and 0.4g of potassium carbonate, heat to 70°C, stir for 8h, centrifuge, wash, and dry to obtain a composite flame retardant filler.
[0039] The composite flame retardant filler was tested by infrared using a Nicoletis50 Fourier transform infrared spectrometer. Figure 2 As shown in the figure, analysis shows that in the infrared spectrum of the composite flame retardant filler, 3100-3000cm -1 The absorption peak of pyridine ring CH appeared at 1734 cm -1The absorption peak of ester group C=O appeared at 1536cm -1 The absorption peak of the pyridine ring skeleton appeared at 1232 cm -1 The absorption peak of P=O appeared at 1125cm -1 The absorption peak of COC appeared at 1021cm -1 The absorption peak of Si-O-Si appears at 587 cm -1 The absorption peak of Al-O appeared at
[0040] Example 1
[0041] Preparation of composite materials
[0042] Step 1: Add 70 g of polypropylene, 4 g of low modulus polypropylene, 1 g of maleic anhydride grafted polypropylene, 0.5 g of calcium stearate, 3 g of functional additives and 2 g of composite flame retardant filler into a high-speed mixer, set the stirring rate to 300 r / min and stir and mix for 25 min to obtain a mixed material;
[0043] Step 2: Add the mixed material into a twin-screw extruder, melt, extrude and granulate, wherein the melting temperature is 160° C. and the screw speed is 200 r / min, to obtain a composite material.
[0044] Example 2
[0045] Preparation of composite materials
[0046] Step 1: Add 75 g of polypropylene, 6 g of low modulus polypropylene, 2 g of maleic anhydride grafted polypropylene, 1 g of calcium stearate, 4 g of functional additives and 3 g of composite flame retardant filler into a high-speed mixer, set the stirring rate to 400 r / min and stir and mix for 30 min to obtain a mixed material;
[0047] Step 2: Add the mixed material into a twin-screw extruder, and perform melting, extrusion, and granulation, wherein the melting temperature is 170° C. and the screw speed is 300 r / min to obtain a composite material.
[0048] Example 3
[0049] Preparation of composite materials
[0050] Step 1: Add 80 g of polypropylene, 8 g of low modulus polypropylene, 2.5 g of maleic anhydride grafted polypropylene, 1 g of calcium stearate, 5 g of functional additives and 4 g of composite flame retardant filler into a high-speed mixer, set the stirring rate to 500 r / min and stir and mix for 35 minutes to obtain a mixed material;
[0051] Step 2: Add the mixed material into a twin-screw extruder, melt, extrude and granulate, wherein the melting temperature is 180° C. and the screw speed is 400 r / min, to obtain a composite material.
[0052] Example 4
[0053] Preparation of composite materials
[0054] Step 1: Add 85 g of polypropylene, 10 g of low modulus polypropylene, 3 g of maleic anhydride grafted polypropylene, 1.5 g of calcium stearate, 6 g of functional additives and 5 g of composite flame retardant filler into a high-speed mixer, set the stirring rate to 600 r / min and stir and mix for 40 min to obtain a mixed material;
[0055] Step 2: Add the mixed material into a twin-screw extruder, melt, extrude and granulate, wherein the melting temperature is 200° C. and the screw speed is 500 r / min, to obtain a composite material.
[0056] Comparative Example 1
[0057] Preparation of composite materials
[0058] Step 1: Add 75 g of polypropylene, 6 g of low modulus polypropylene, 2 g of maleic anhydride grafted polypropylene, 1 g of calcium stearate, and 3 g of composite flame retardant filler into a high-speed mixer, set the stirring rate to 400 r / min, and stir and mix for 30 minutes to obtain a mixed material;
[0059] Step 2: Add the mixed material into a twin-screw extruder, and perform melting, extrusion, and granulation, wherein the melting temperature is 170° C. and the screw speed is 300 r / min to obtain a composite material.
[0060] Comparative Example 2
[0061] Preparation of composite materials
[0062] Step 1: Add 75 g of polypropylene, 6 g of low modulus polypropylene, 2 g of maleic anhydride grafted polypropylene, 1 g of calcium stearate, and 4 g of functional additives into a high-speed mixer, set the stirring rate to 400 r / min, and stir and mix for 30 minutes to obtain a mixed material;
[0063] Step 2: Add the mixed material into a twin-screw extruder, and perform melting, extrusion, and granulation, wherein the melting temperature is 170° C. and the screw speed is 300 r / min to obtain a composite material.
[0064] Comparative Example 3
[0065] Preparation of composite materials
[0066] Step 1: Add 75 g of polypropylene, 6 g of low modulus polypropylene, 2 g of maleic anhydride grafted polypropylene, 1 g of calcium stearate, 4 g of anisaldehyde and 3 g of composite flame retardant filler into a high-speed mixer, set the stirring rate to 400 r / min and stir and mix for 30 min to obtain a mixed material;
[0067] Step 2: Add the mixed material into a twin-screw extruder, and perform melting, extrusion, and granulation, wherein the melting temperature is 170° C. and the screw speed is 300 r / min to obtain a composite material.
[0068] Comparative Example 4
[0069] Preparation of composite materials
[0070] Step 1: Add 75 g of polypropylene, 6 g of low modulus polypropylene, 2 g of maleic anhydride grafted polypropylene, 1 g of calcium stearate, 4 g of functional additives and 3 g of medical stone into a high-speed mixer, set the stirring rate to 400 r / min and stir and mix for 30 min to obtain a mixed material;
[0071] Step 2: Add the mixed material into a twin-screw extruder, and perform melting, extrusion, and granulation, wherein the melting temperature is 170° C. and the screw speed is 300 r / min to obtain a composite material.
[0072] Performance Testing
[0073] The composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were tested for performance, and the test results are shown in the following table:
[0074]
[0075] The impact strength was tested according to GB / T 1843-2008 to determine the impact resistance of the composite material. The tensile strength was tested according to GB / T 1040.1-2018 to determine the mechanical properties of the composite material. The composite material was placed at room temperature for 60 days and then aged in an aging box for 12 hours at 120°C. The tensile strength was tested again to determine the antioxidant properties of the composite material. The oxygen index was tested according to GB / T 2406.2-2009 to determine the flame retardant properties of the composite material.
[0076] It can be seen from the analysis of the above table that by adding the functional additives and composite flame retardant fillers prepared by the present invention, a polypropylene composite material with high strength, excellent impact resistance, antioxidant properties and flame retardant properties can be prepared. Comparative Example 1 does not add any functional additives, and has poor impact resistance and antioxidant properties, but adds a composite flame retardant filler, so it has high strength and excellent flame retardant properties; Comparative Example 2 does not add any composite flame retardant filler, and has poor mechanical properties and flame retardant properties, but adds a functional additive, so it has excellent impact resistance and antioxidant properties; Comparative Example 3 adds anisaldehyde, and the antioxidant properties and impact resistance decrease, which is due to the precipitation of the small molecule antioxidant anisaldehyde, resulting in the decrease in antioxidant properties, and anisaldehyde is not grafted with the terminal vinyl hyperbranched polyester, and cannot form a polymer network with the polypropylene matrix under the action of the compatibilizer, so the impact resistance decreases, but the composite flame retardant filler is added, so it has high strength and excellent flame retardant properties; Comparative Example 4 adds medical stone, and there is agglomeration phenomenon when it is directly added to the polypropylene matrix without modification, so the mechanical properties and flame retardant properties are poor, but the functional additive is added, and the antioxidant properties and impact resistance are excellent.
[0077] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A high-strength composite material for manufacturing a plastic housing, characterized in that: The invention comprises the following raw materials in parts by weight: 70-85 parts of polypropylene, 4-10 parts of low modulus polypropylene, 1-3 parts of compatibilizer, 0.5-1.5 parts of lubricant, 3-6 parts of functional additives and 2-5 parts of composite flame retardant filler.
2. The high-strength composite material for manufacturing a plastic shell according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene; the lubricant is any one of calcium stearate, magnesium stearate or zinc stearate.
3. The high-strength composite material for manufacturing a plastic shell according to claim 1, characterized in that: The method for preparing the functional additive comprises the following steps: S1. Add the terminal vinyl hyperbranched polyester, mercaptoethylamine and photoinitiator into toluene, stir evenly, and react under ultraviolet light for 1-3 hours. After the reaction is completed, separate the product to obtain an intermediate material; S2. Add the intermediate material, anisaldehyde and triethylamine into methanol, stir evenly, and react for 2-4 hours at room temperature. After the reaction is completed, remove the solvent by distillation under reduced pressure, wash, and obtain a functional additive.
4. The high-strength composite material for manufacturing a plastic housing according to claim 3, characterized in that: In S1, the photoinitiator is any one of benzoin bis ether, benzoin isobutyl ether or benzoin isopropyl ether.
5. The high-strength composite material for manufacturing a plastic housing according to claim 1, characterized in that: The preparation method of the composite flame retardant filler comprises the following steps: Step A, adding medical stone to a 0.5-1 mol / L hydrochloric acid solution, then placing the system in an ultrasonic cleaning machine for 10-15 minutes, filtering, washing, and drying to obtain activated medical stone; Step B, uniformly dispersing the activated medical stone in N,N-dimethylformamide, introducing nitrogen, adding 6-chloropyridine-3-carbonyl chloride and a catalyst, stirring at room temperature for 5-6 hours, filtering, washing, and drying to obtain modified medical stone; Step C, adding modified medical stone to dimethyl sulfoxide, stirring evenly, introducing nitrogen, adding dimethyl hydroxymethylphosphonate and an alkaline catalyst, heating to 60-80° C., stirring for 6-8 hours, centrifuging, washing, and drying to obtain a composite flame retardant filler.
6. The high-strength composite material for manufacturing a plastic housing according to claim 5, characterized in that: In step B, the catalyst is pyridine or triethylamine.
7. The high-strength composite material for manufacturing a plastic housing according to claim 5, characterized in that: In step C, the alkaline catalyst is potassium carbonate or sodium carbonate.
8. A method for preparing a high-strength composite material for manufacturing a plastic housing as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add polypropylene, low modulus polypropylene, compatibilizer, lubricant, functional additive and composite flame retardant filler into a high speed mixer, set the stirring speed to 300-600 r / min, stir and mix for 25-40 minutes, and obtain a mixed material; Step 2: Add the mixed material into a twin-screw extruder, and obtain a composite material through melting, extrusion and granulation.
9. The method for preparing a high-strength composite material for manufacturing a plastic housing according to claim 8, characterized in that: The twin-screw extruder has a melting temperature of 160-200° C. and a screw speed of 200-500 r / min.
Citation Information
Patent Citations
A flame-retardant PP composite material and its preparation method
CN112225985B
Cited By
Wear-resistant and impact-resistant PP (polypropylene) composite material and preparation process thereof
CN120795474A
